Gastro-jejunal with jejuno-jejunal anastomoses for treatment of the case of cascade stomach - Bondar, Oleksandr M.; Kovalska, Olena O.; Paneque, Yalisa H. (International Surgery Journal, 2023)
The cascade stomach (CS) is characterized as a changing of the gastric cavity to the “hour glass" two chambers formation. The disease is well presented in the gastroenterological and radiological literature. In the case of failure of conservative treatment, the surgery is indicated. Unfortunately, the information of operative treatment of this condition is limited. We present the case of the CS successfully treated by creation of the gastro-jejunal and jejuno-jejunal anastomoses.